Hemodynamics and Gas Exchange in Hemorrhagic Shock and Hyperbaric Oxygenation (Experimental Study) - Yu. M. Tumanovsky (Общая реаниматология, 2007)
Objective: to study the specific features of correction of hemodynamic and oxygen homeostasis in anemic animals exposed to hyperbaric oxygenation (HBO).Materials and methods. Experiments were made on 30 mongrel dogs in 2 series of experiments: 1) 15 animals under hemorrhagic shock (a control group); 2) 15 anemic animals exposed to HBO (pO=300 kPa; 60-min session). Cardiac index (CI), left ventricular stroke output index (LVSOI), myocardial tension index (MTI), heart rate, and blood pressure (BP) were determined in all the animals at the baseline, in 30- and 90-minute shock and after oxygenation. The Astrup micromethod was used to estimate oxygen tension (PaO2, PvO2) and content (CaO2, CvO2) in arterial and venous blood, arteriovenous (AV) oxygen difference, and tissue oxygen-utilization coefficient (TOUC).Results. In the untreated anemic animals, the reduction in central hemodynamic parameters (CI, LVSOI) was attended by the increase in MTI, suggesting significant impairments of metabolic processes in the myocardium and its diminished contractility. Oxygen homeostatic disorder was characterized by a noticeable increase in AV oxygen difference and TOUC with decreases in PvO2 and CvO2. After oxygenation (minute 5) there were positive changes in oxygen homeostatic parameters with the hemodynamic parameters being normalized, which contributed to the recovery of myocardial functional activity and to the diminution of manifestations of tissue hypoxia.Conclusion. HBO used in anemic animals promotes the recovery of hemodynamic homeostasis due to the activation of oxygen-dependent myocardial metabolic processes and the reduction of tissue hypoxic manifestations.